Chromosomal mapping of rDNAs and H3 histone sequences in the grasshopper rhammatocerus brasiliensis (acrididae, gomphocerinae): extensive chromosomal dispersion and co-localization of 5S rDNA/H3 histone clusters in the A complement and B chromosome - Oliveira, Nathalia L.; Cabral-de-Mello, Diogo Cavalcanti [UNESP]; Rocha, Marilia F.; Loreto, Vilma; Martins, Cesar [UNESP]; Moura, Rita C. (Biomed Central Ltd., 2011)
Background: Supernumerary B chromosomes occur in addition to standard karyotype and have been described in about 15% of eukaryotes, being the repetitive DNAs the major component of these chromosomes, including in some cases the presence of multigene families. To advance in the understanding of chromosomal organization of multigene families and B chromosome structure and evolution, the distribution of rRNA and H3 histone genes were analyzed in the standard karyotype and B chromosome of three populations of the grasshopper Rhammatocerus brasiliensis.Results: The location of major rDNA was coincident with the previous analysis for this species. on the other hand, the 5S rDNA mapped in almost all chromosomes of the standard complement (except in the pair 11) and in the B chromosome, showing a distinct result from other populations previously analyzed. Besides the spreading of 5S rDNA in the genome of R. brasiliensis it was also observed multiple sites for H3 histone genes, being located in the same chromosomal regions of 5S rDNAs, including the presence of the H3 gene in the B chromosome.Conclusions: Due to the intense spreading of 5S rRNA and H3 histone genes in the genome of R. brasiliensis, their chromosomal distribution was not informative in the clarification of the origin of B elements. Our results indicate a linked organization for the 5S rRNA and H3 histone multigene families investigated in R. brasiliensis, reinforcing previous data concerning the association of both genes in some insect groups. The present findings contribute to understanding the organization/evolution of multigene families in the insect genomes.
Keywords: evolution; genome; cytogenetics; multigene family